Study on General Governing Equations of Computational Heat Transfer and Fluid Flow (Communications in Computational Physics, 2012)
The governing equations for heat transfer and fluid flow are often formulated in a general form for the simplification of discretization and programming, whichhas achieved great success in thermal science and engineering. Based on the analysisof the popular general form of governing equations, we found that energy conservation cannot be guaranteed when specific heat capacity is not constant, which may leadto unreliable results. A new concept of generalized density is put forward, based onwhich a new general form of governing equations is proposed to guarantee energyconservation. A number of calculation examples have been employed to verify validation and feasibility